Determinants analysis of earnings response coefficient: Empirical study in Indonesia - Sintya Puspita Dewi; Abriyani Puspaningsih (Accounting Department, Faculty of Business and Economics, Universitas Islam Indonesia, 2019)
This study aims to analyze determinants of earnings response coefficient. Independent variables used in this research are company size, company’s growth, profitability and financial leverage while the dependent variable is earnings response coefficient. The type of the research is quantitative research. The data used in this research is secondary data. The populations in this study are manufacturing companies listed in Indonesia Stock Exchange. The method of analysis that used in this research is multiple regressions. The results shows that company’s growth has a positive effect on the earnings response coefficient. While the company size, profitability, financial leverage do not have any effect on the earnings response coefficient. This study indicates that high growth companies will give a good signal to investors.